Characterization of a spirit beverage produced with strawberry tree (Arbutus unedo L.) fruit and aged with oak wood at laboratorial scale - Anjos, O. (2021)
Arbutus unedo spirit is a valuable product in Mediterranean countries. This spirit is usually marketed in Portugal without wood ageing. This work aims to characterize the ageing effect on the Arbutus unedo spirit, for three and six months with oak wood (Quercus robur L.) submitted to different toasting levels, based on its chemical composition and its sensory properties. For this purpose, several parameters were analysed: acidity, pH, dry extract, and volatile compounds (methanol, acetaldehyde, ethyl acetate and fusel alcohols). The volatile compounds were identified by GC-MS and quantified by GC-FID. Sensory analysis was performed by a trained panel, who have profiled this beverage, as well as the changes acquired during ageing. Spectroscopic techniques, namely FTIR–ATR, were applied to discriminate the different beverages produced. The results highlighted an increase in Arbutus unedo spirit’s quality with the wood contact, mainly based on the sensory attributes. Additionally, they showed that the best beverages were produced using oak wood with medium toasting levels during three months of ageing